Alterations in Lipid-Lipoprotein Fractions and Antioxidant Status by Lycopene and its Blends with Rice Bran Oil in Nutritionally Induced Hyperlipidemic Animal Model - Chauhan, Komal (Journal of Nutritional Therapeutics, 2017)
Nutrition Transition in the latter half of 20th century has prompted profound shift from traditional dietary pattern of fibre rich foods to increased consumption of energy dense, high fat and low fibre foods. Resultant oblivious nutritional environment coupled with physical inactivity has abridged the gap between health and chronic diseases. Consequently, the paradigm of treatment from pharmaceuticals has shifted to neutraceuticals and a large proportion of populace is resorting to cost effective treatments from natural sources that can contribute effectually in combating these dreadful diseases. The present study was undertaken to evaluate the efficacy of blends of lycopene and rice bran oil (RBO) on alteration in lipid metabolism and oxidative stress biomarkers in high fat high cholesterol diet fed albino rats. The rats were supplemented with lycopene (30mg/kg/day) singly and blend of lycopene (30mg/kg/day) and rice bran oil (100ml/kg/day) for 6 weeks. Results indicate that lycopene enriched diets significantly (p≤0.05) improved altered parameters, however, the effect was more pronounced in animals reared on blends of lycopene and RBO. The therapeutic potential of lycopene and RBO can be tapped as preventive and protective therapy against the detrimental effects of high fat diets consumed globally.